EDUKASI APLIKASI DIGITAL InfoBMKG DAN TEKNOLOGI MKG UNTUK GENERASI TANGGAP BENCANA - Niken Wahyuni; Mugiyono; Chandra Dwi Pratomo; Diah Ariefianty; Tukiyat; Agus Tianoto Damar; Abdul Aziz; Nofandi Kodyatmoko (Abdi Jurnal Publikasi, 2025)
This community service program aims to enhance students’ literacy in meteorology, climatology, and geophysics (MCG), as well as improve their ability to utilize the InfoBMKG mobile application as an official and reliable source of weather, climate, and earthquake information. The activity was carried out at SMA IT Baitul Ilmi Bekasi through an educational and participatory approach consisting of awareness sessions on MCG concepts, demonstrations of the InfoBMKG application, discussions, and pre-test and post-test evaluations. A total of 40 students participated in this program. The evaluation results showed a 38% increase in participants’ understanding after the intervention. Moreover, most students demonstrated the ability to independently access weather, climate, and earthquake information, and they showed improved digital literacy, especially in identifying valid data and distinguishing it from hoaxes. Overall, this activity effectively strengthened MCG literacy among high school students and promoted the use of official data in disaster preparedness. The program is recommended to be continued and expanded to other schools as an effort to support disaster risk reduction and strengthen anti-hoax awareness among youth.